Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 8 - Section 8.2 - The Quadratic Formula - Exercise Set - Page 608: 50


$x=${$-3- i\sqrt 3,-3+i\sqrt 3$}

Work Step by Step

Given: $x(x+6)=-12$ Re-write the given equation as: $x^2+6x=-12$ This implies that $x^2+6x+12=0$ Factorize the expression with the help of quadratic formula. Quadratic formula suggests that $x=\dfrac{-b \pm \sqrt{b^2-4ac}}{2a}$ This implies that $x=\dfrac{-(6) \pm \sqrt{(6)^2-4(1)(12)}}{2(1)}$ or, $x=\dfrac{-6 \pm \sqrt {-12}}{2}$ or, $x=${$\dfrac{-6- 2i\sqrt 3}{2},\dfrac{-6+ 2i\sqrt 3}{2}$} Hence, our solution set is: $x=${$-3- i\sqrt 3,-3+i\sqrt 3$}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.